Odpowiedzi

2010-01-26T18:59:41+01:00
(-4)-(-19)=-4+19=15
(-8)-(-2)=-8+2=-6
(-10)-(-14)=-10+14=4
-(-15)-(-14)=15+14=29


a)(-2)+(-8)-(6)-(-4)= -10-6+4=-12
b) (12)-(-16)-(6)+(20)= 12+16-6+20= 42
c) -20-(-5)+(-17)-(-3)=-20+5-17+3=-29
d) (-4+7)-(-10-12)=3+22=25
e) -(-11+14)-(16-13)=-3-3=-9
f) -(12-6)+(4-9)=-6-5=-11
2010-01-26T19:32:23+01:00
(-4)-(-19)=-23
(-8)-(-2)=-10
(-10)-(-14)=-24
-(-15)-(-14)=29

a)(-2)+(-8)-(6)-(-4)=-10-6+4=-8
b) (12)-(-16)-(6)+(20)=12+16-6+20=28-26=2
c) -20-(-5)+(-17)-(-3)=-20+5-17+3=-25-20=-5
d) (-4+7)-(-10-12)=-11+2=-13
e) -(-11+14)-(16-13)=25-3=22
f) -(12-6)+(4-9)=-6+5=-11